2019
DOI: 10.1136/neurintsurg-2019-015308
|View full text |Cite
|
Sign up to set email alerts
|

Patients with low Alberta Stroke Program Early CT Score (ASPECTS) but good collaterals benefit from endovascular recanalization

Abstract: BackgroundBenefit of thrombectomy in patients with a low initial Alberta Stroke Program Early CT Score (ASPECTS) is still uncertain. We hypothesized that, despite low ASPECTS, patients may benefit from endovascular recanalization if good collaterals are present.MethodsIschemic stroke patients with large vessel occlusion in the anterior circulation and an ASPECTS of ≤5 were analyzed. Collateral status (CS) was assessed using a 5-point-scoring system in CT angiography with poor CS defined as CS=0–1. Clinical out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 33 publications
3
50
0
Order By: Relevance
“…On the contrary, the baseline ASPECTS between the two groups in our study were comparable (p ¼ 0.545), suggesting that there might be additional factors which should be considered: clot burden, thrombus length/composition, and presence of collaterals. 19,20 A late M1 division was associated with atherosclerotic disease as the main cause of AIS with a higher rate of tandem occlusion or stenosis (15% vs. 5.7%, p ¼ 0.060). As such, no impact on angiographic or clinical outcome was found.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the baseline ASPECTS between the two groups in our study were comparable (p ¼ 0.545), suggesting that there might be additional factors which should be considered: clot burden, thrombus length/composition, and presence of collaterals. 19,20 A late M1 division was associated with atherosclerotic disease as the main cause of AIS with a higher rate of tandem occlusion or stenosis (15% vs. 5.7%, p ¼ 0.060). As such, no impact on angiographic or clinical outcome was found.…”
Section: Discussionmentioning
confidence: 99%
“…One hundred and twenty-nine patients with a CS of 0-2 were included (CS 0=37; CS 1=50; CS 2=42). The mean (SD) age of these patients was 73 (12), and the median NIHSS was 18 (IQR: [15][16][17][18][19][20]. Admission imaging was performed after a median time of 3 hours after symptom onset (IQR: 2-4).…”
Section: Resultsmentioning
confidence: 99%
“…12 The results of this study emphasise that patients with poor intracranial collaterals, who are often excluded in stroke trials, may still benefit from thrombectomy, with improved clinical outcome. 19 Although the effect of vessel recanalisation on oedema formation has already been discussed, the exact mechanisms of this phenomenon remain uncertain. Factors such as age or blood glucose concentration have been discussed as important mediators of oedema formation, but the potential role of collaterals has not yet been described.…”
Section: Discussionmentioning
confidence: 99%
“…In this background, there is considerable interest and debate on the impact of collaterals on clinical outcomes after EVT in patients with low ASPECTS score . A recent study by Broocks et al demonstrated that pre-treatment collateral status could be used as a selection criterion for EVT treatment in low ASPECTS patients (Broocks et al, 2020). Authors found that in patients with ASPECTS of ≤5, patients could still benefit from EVT if good collaterals are present as good collaterals were directly associated with attenuated oedema formation with improved clinical outcome (Broocks et al, 2020).…”
Section: Collateral Assessment With Static and Dynamic Gradingmentioning
confidence: 99%
“…A recent study by Broocks et al demonstrated that pre-treatment collateral status could be used as a selection criterion for EVT treatment in low ASPECTS patients (Broocks et al, 2020). Authors found that in patients with ASPECTS of ≤5, patients could still benefit from EVT if good collaterals are present as good collaterals were directly associated with attenuated oedema formation with improved clinical outcome (Broocks et al, 2020). Given the small sample size in this study, future prospective studies on the relatively larger dataset are required to validate these findings and identify the optimal EVT eligibility criterion in lower ASPECTS patients.…”
Section: Collateral Assessment With Static and Dynamic Gradingmentioning
confidence: 99%